Strategic Environmental Assessment : Improving Water Resources Governance and Decision Making - Hirji, Rafik; Davis, Richard (World Bank, Washington, DC, 2014)
The overall goal of this report is to assist water resources and environment professionals within the Bank and client countries to use Strategic environmental assessment (SEAs) to effectively implement the principles of Integrated water resources management (IWRM). It (a) delineates environmental issues related IWRM; (b) identifies opportunities for SEAs to addressing these environmental issues; (c) uses the literature and ten Bank and non-Bank case studies to identify procedural and substantive factors and institutional drivers that lead to effective SEAs in the water sector at the policy, strategy, program, and plan levels; (d) reviews four national and state water policies to understand the inclusions of environment; (e) observes the introduction of SEAs in a developing country as an in-depth pilot study to identify practical issues arising from the introduction of SEAs for the water sector; and (f) recommends how the Bank can expand the use of SEAs to improve the integration of environmental issues in water resources investments.